Experimental thermal and environmental impact performance evaluations of hydrogen-enriched fuels for power generation - Karasu, Huseyin; Erdemir, Dogan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
The transition to a low-carbon energy future requires a multi-faceted approach, including the enhancement of existing power generation technologies. This study provides a comprehensive experimental evaluation of hydrogen enrichment as a strategy to improve the performance and reduce the emissions of a power generator. A 3.65 kW power generator that is equipped with spark-ignition engine is systematically tested with five distinct base fuels: gasoline, propane, methane, ethanol, and methanol. Each fuel is volumetrically blended with pure hydrogen in ratios of 5 %, 10 %, 15 %, and 20 % using a custom-developed dual-fuel carburetor. The key parameters, including exhaust emissions (CO2, CO, HC, NOx), cylinder exit temperature, electrical power output, and thermodynamic efficiencies (energy and exergy), are meticulously measured and analyzed. The results reveal that hydrogen enrichment is a powerful tool for decarbonization, consistently reducing carbon-based emissions across all fuels. At a 20 % hydrogen blend, CO2 emissions are reduced by 22-31 %, CO emissions by 39-60 %, and HC emissions by 21-60 %. This environmental benefit, however, is accompanied by a critical trade-off: a severe increase in NOx emissions, which rose by 200-420 % due to significantly elevated combustion temperatures. The power outputs are increased by 2-16 %, with hydrogen addition enabling lower-energy-density fuels like methane and propane to achieve performance parity with gasoline. Thermodynamic analysis confirms these gains, with energy efficiency showing marked improvement, particularly for methane, which has increased from 42.0 % to 49.9 %. While hydrogen enrichment presents a viable pathway for enhancing engine performance and reducing the carbon emissions of power generators, the profound increase in NOx necessitates the integration of advanced control and after-treatment systems for its practical and environmentally responsible deployment.
Keywords: Hydrogen enrichment; Alternative fuels; Spark-ignition engine; Emission control; Nitrogen oxides; Power generation; ENGINE; COMBUSTION; EMISSIONS; ETHANOL; Thermodynamics; Energy & Fuels; Engineering; Mechanics